2010
DOI: 10.1002/ejic.201000191
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Encapsulation or Host–Guest Behavior of Aromatic Molecules in Hexanuclear Arene Ruthenium Prisms

Abstract: Cationic arene ruthenium metallaprisms of the general formula [Ru 6 (p-cymene) 6 (tpt) 2 (OOʝOO) 3 ] 6+ {tpt = 2,4,6-tris(4-pyridyl)-1,3,5-triazine; OOʝOO = 9,10-dioxo-9,10-dihydroanthracene-1,4-diolato ) and car-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Indeed, in this complex the lengths of the CO bonds are between 1.27(1) and 1.32(2) , which suggests an intermediate bond order between single (~1.40 ) and double 20 ). [23] In addition to these C=O signals, strong absorptions due to the stretching vibrations of the triflate anions (1260 (s), 1030 (s), 638 cm 1 (m)) are observed in the infrared spectra of all the salts…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Indeed, in this complex the lengths of the CO bonds are between 1.27(1) and 1.32(2) , which suggests an intermediate bond order between single (~1.40 ) and double 20 ). [23] In addition to these C=O signals, strong absorptions due to the stretching vibrations of the triflate anions (1260 (s), 1030 (s), 638 cm 1 (m)) are observed in the infrared spectra of all the salts…”
Section: Resultsmentioning
confidence: 85%
“…[19,20] The cavities of [1-3] 6 + are of an equivalent size, but the use of different OO\OO connectors controls their portal size, thus modulating the dynamics of the host-guest systems. The encapsulation of PdA C H T U N G T R E N N U N G (acac) 2 and pyrene-R in these cages requires the addition of silver triflate to the corresponding dinuclear arene-ruthenium complexes [Ru 2 (p-iPrC 6 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the donor 3 shows no absorption at the lower energy region (> 300 nm), the electronic transition in 4 and 5 could be ascribed to mixed intra- and intermolecular π-π* and MLCT transitions associated with the arene-Ru moiety. [18] …”
Section: Resultsmentioning
confidence: 99%
“…Therrien et al were able to encapsulate different planar aromatic molecules such as phenanthrene, pyrene, fluoranthene, benzo[ e ]pyrene, triphenylene, and coronene into the hydrophobic cavity of a series of cationic (arene)ruthenium-based trigonal prisms [Ru 6 (η 6 - p -cymene) 6 ( 285 ) 2 ( OO ∩ OO ) 3 ] 6+ 363-367 [ OO ∩ OO = 2,5-dihydroxy-1,4-benzoquinonato (dhbq), 2,5-dichloro-3,6-dihydroxy-1,4-benzoquinonato (dchq), 5,8-dihydroxy-1,4-naphthoquinonato (dhnq), 9,10-dihydroxy-1,4-anthraquinonato (dhaq), or 6,11-dihydroxy-naphthacene-5,12-dionato(dhtq)] by using them as templating guests. 428,429 Empty trigonal prismatic cages 363-367 have been used for host-guest studies and have shown that small aromatic molecules (phenanthrene and pyrene) show rapid inclusion into the hydrophobic cavities of the cages upon gradual addition of guests. However, molecules that are too large to exit the portal of the cages get permanently incarcerated, thus giving rise to stable carceplex systems.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%